User-Centered Mobile Navigation: Evaluating Local Usability for Improved UX - Yunianto, Irdha (Teknik: Jurnal Ilmu Teknik dan Informatika, 2025)
Mobile navigation interfaces continue to be plagued by a key usability problem, particularly when widely accepted design traditions fail to address the specific requirements and mental models of local user populations. This research addresses this significant limitation by using a comprehensive user-focused measurement framework to identify and investigate context-dependent navigation problems in mobile applications. The research employed a multi-method qualitative approach, using in-depth questionnaires, semi-structured interviews, and laboratory-based usability testing of 15 participants on an interactive Figma prototype that simulated real-world navigation tasks. Our analysis, step by step, revealed significant navigation issues in the local context, as evidenced by a 73% task-completion rate and an average participant error of 2.8 across the core navigation tasks. The most significant usability issues were ambiguous iconography, inconsistent application of platform design patterns, and insufficient system feedback mechanisms. The results conclusively demonstrate that localized usability testing is not merely beneficial but necessary while creating genuinely good and accessible mobile experiences. The study provides a replicable, practical context-aware evaluation approach and tangible, right-now-applicable design recommendations, such as enhancing icons with descriptive text labels and using instant visual feedback mechanisms. The study provides developers and designers with tangible takeaways for significantly enhancing navigation user experience without sacrificing methodological availability or implementation convenience across different development environments.